Identification of a Novel c-Myc Inhibitor 7594-0037 by Structure-Based Virtual Screening and Investigation of Its Anti-Cancer Effect on Multiple Myeloma - Yao R; Xie Y; Sun X; Zhang M; Zhou J; Liu L; Gao J; Xu K (Dove Medical Press, 2020)
Ruosi Yao,1,2 Yu Xie,1 Xiaoyang Sun,1 Menghui Zhang,1 Jian Zhou,1 Linlin Liu,3 Jian Gao,4 Kailin Xu1,2 1Blood Diseases Institute, Xuzhou Medical University, Xuzhou, Jiangsu, People’s Republic of China; 2Department of Hematology, The Affiliated Hospital of Xuzhou Medical University, Xuzhou, Jiangsu, People’s Republic of China; 3College of Medical Imaging, Xuzhou Medical University, Xuzhou, Jiangsu, People’s Republic of China; 4Jiangsu Key Laboratory of New Drug Research and Clinical Pharmacy, Xuzhou Medical University, Xuzhou, Jiangsu, People’s Republic of ChinaCorrespondence: Kailin XuBlood Diseases Institute, Xuzhou Medical University, Xuzhou, Jiangsu, People’s Republic of ChinaEmail lihmd@163.comJian GaoJiangsu Key Laboratory of New Drug Research and Clinical Pharmacy, Xuzhou Medical University, Xuzhou, Jiangsu, People’s Republic of ChinaEmail 18626042662@163.comIntroduction: Multiple myeloma (MM) is an extremely malignant and incurable hematological cancer. Increased expression of the c-Myc oncoprotein is closely associated with shorter overall survival of MM patients, implying that c-Myc is a potential therapeutic target.Main Methods: We identified a potential c-Myc inhibitor 7594– 0037 by structure-based virtual screening from the ChemDiv database. CCK8 assay and flow cytometry were used to detect MM cell viability, cell cycle and apoptosis. Q-PCR and Western blot were used to measure corresponding mRNA and protein expression levels. Protein stability assay measured the stability of c-Myc.Results: Compound 7594– 0037 exhibited stronger anti-proliferative activity against MM cells, and induced MM cell cycle G2 phase arrest and apoptosis. More importantly, compound 7594– 0037 overcame myeloma resistance to bortezomib and exhibited a synergistic effect with bortezomib, resulting in increased MM cell death. The mechanism consists of compound 7594– 0037 facilitating c-Myc protein degradation via decreasing the c-Myc S62 phosphorylation levels mediated by PIM1 kinase. Molecular dynamics simulation with the c-Myc/7594-0037 complex showed that compound 7594– 0037 bound tightly to the N-terminus of c-Myc, and blocked the binding interaction of the two termini of c-Myc, which resulted in c-Myc entering into an unstable state.Conclusion: Overall, our study provides preliminary data for compound 7594– 0037, which can be used as a novel c-Myc inhibitor and is a potential candidate therapeutic drug for multiple myeloma.Keywords: multiple myeloma, c-Myc inhibitor, virtual screening, drug resistance, apoptosis